Perfil clínico e funcional da pessoa idosa que acessa uma unidade de reabilitação - Gularte, Ana Cristina (2022)
From the increase in life expectancy of the world population emerges the need for attention on the part of society and health systems to find a way to adapt to this new reality. It is important to “think, discuss, plan and implement” actions that promote the quality of life of this population. In this sense, rehabilitation emerges as a viable alternative, as it is a set of actions that help to preserve the subject's functionality, autonomy and independence. Objective: to characterize the care provided to the elderly person in a rehabilitation unit, based on the premises of geriatric rehabilitation, seeking to qualify multiprofessional approaches that aim to reduce functional losses. Methodology: this is a quantitative, descriptive research, through document analysis, of elderly people in a rehabilitation program in a teaching hospital. Sociodemographic variables were analyzed (age, gender, marital status, family group, education, occupation and color or ethnicity), life habits (alcoholism, smoking, physical and sexual activity), functional evaluation by means of scales and instruments (Mini Mental State Examination, Verbal Fluency Test, Body Mass Index, Calf Circumference, Geriatric Depression Scale, Katz Index, Lawton Scale, Time up and go test, among others). Those of the attending professionals were also identified. The data were plotted in an Excel spreadsheet and analyzed using the SPSS Statistical program (Version 21.0). Results: A total of 47 elderly people who were treated at the service, 55.3% were men, 93.6% were white, and the overall mean age was 69.87 years. Most of the elderly people had as marital status married 57.4%, where 57.9% were retired and 55.3% had incomplete elementary school education. Life habits were evaluated in 63.8% of the patients; of these, 13.3% were active smokers, 10% used alcoholic beverages, 20% practiced physical activity, and reported having an active sex life. The prevalence of underlying diseases was of cardiovascular disease (n=11), lung disease (n=10), osteoarticular disease (n=10), cancer (n=7), among others. Regarding associated comorbidities, the highest prevalence was of cardiovascular disease 74.4%, endocrine 34.1%, osteoarticular and psychiatric 19.2% each, pulmonary 17%, among others. The calf circumference analysis identified a median of 36.50 (minimum 30, maximum 42-median 36.08 (±3.70), where the majority of the elderly had CP >31 cm. Polypharmacy reached 91.5%. The care provided in the rehabilitation unit was mostly provided by physical therapists, nurses, and geriatricians. Conclusion: This study outlined the clinical and functional profile of the elderly in rehabilitation and the professionals involved in geriatric rehabilitation. It is envisaged that new studies will be carried out, and from there, more investment will be made in the complexity of care directed to geriatric rehabilitation, as recommended by the relevant guidelines.